2011
DOI: 10.1097/aln.0b013e31822fd1f1
|View full text |Cite
|
Sign up to set email alerts
|

Potential Adverse Ultrasound-related Biological Effects

Abstract: Ultrasound energy exerts important cellular, genetic, thermal, and mechanical effects. Concern about the safety of ultrasound prompted several agencies to devise regulatory limits on the machine output intensities. The visual display of thermal and mechanical indices during ultrasound imaging provides an aid to limit the output of the machine. Despite many animal studies, no human investigations conducted to date have documented major physiologic consequences of ultrasound exposed during imaging. To date, ultr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
94
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 138 publications
0
94
1
Order By: Relevance
“…As such, we reanalyzed the data (SctO 2 against SjvO 2 ) by using a Bland-Altman plot with multiple measurements per subject. 3 Nevertheless, we found little change in the 95% limit of agreement (from −37.8% to +23.6% with mean difference −7.2) compared with that (−38.2%, 23.8% with mean difference −7.2) of our previous data. 1 In fact, we used a Bland-Altman plot with multiple measurements per subject in another study and demonstrated a lack of agreement of SctO 2 and SjvO 2 values during the surgery in the beach chair position.…”
Section: Correspondence Correspondencecontrasting
confidence: 48%
See 2 more Smart Citations
“…As such, we reanalyzed the data (SctO 2 against SjvO 2 ) by using a Bland-Altman plot with multiple measurements per subject. 3 Nevertheless, we found little change in the 95% limit of agreement (from −37.8% to +23.6% with mean difference −7.2) compared with that (−38.2%, 23.8% with mean difference −7.2) of our previous data. 1 In fact, we used a Bland-Altman plot with multiple measurements per subject in another study and demonstrated a lack of agreement of SctO 2 and SjvO 2 values during the surgery in the beach chair position.…”
Section: Correspondence Correspondencecontrasting
confidence: 48%
“…3 Our data showed significant changes in intraorbital temperature after exposure to the nonorbital rated Sonosite Micromaxx 6-13 MHz linear transducer (Bothell, WA).…”
Section: Ultrasound Investigation and The Eyementioning
confidence: 99%
See 1 more Smart Citation
“…The pain physician should limit and minimize the use of ultrasound to only the time necessary to perform each procedure. 16 …”
Section: Contraindicationsmentioning
confidence: 99%
“…However, long-term clinical effects of tissue heating and cavitation is not known yet. [11] In pain treatment, US is used in interventions performed on peripheral nerves, neuroaxial structures and musculoskeletal structures. These common interventions are listed below:…”
Section: Introductionmentioning
confidence: 99%